Method of assessment of polymers biodegradability for investigation of their usability to organic recovery by composting - Kikolski, P.; Dłuska-Smolik, E.; Bolińska, A. (Polimery, 2022)
The results of experiments aimed at elaborating the procedure of preliminary assessment of biodegradability were presented. The assessment was needed for estimation of usability for composting of packaging materials made of biodegradable polymers. Pilot test stand for measuring of polymer biodegradation during composting was designed and installed (Fig. 1). Test of selected polymer biodegradation, with microcrystalline cellulose as reference material, was carried out in the stand (Table 1). Comparative curves of CO2 formation (Fig. 3) and biodegradation curves (Fig. 4) were prepared. The results of biodegradation degree calculation either on the basis of amount of evolved CO2 measurement or standardized measurement of organic substance weight loss were compared (Table 2). Technical limitations making impossible the proper assessment of biodegradation course in the stand used were discussed and the solutions allowing to eliminate the shortcomings observed were pointed out.